2020
DOI: 10.1021/acsami.0c04854
|View full text |Cite
|
Sign up to set email alerts
|

Sputtered SrxNbO3 as a UV-Transparent Conducting Film

Abstract: Expanding the application space of transparent electrodes toward the ultraviolet range has been found challenging when utilizing the conventional approach to degenerately dope semiconductors with band gaps larger than ZnO or In2O3. Here, it is shown that the correlated metal Sr x NbO3 with x < 1 is ideally suited as a UV-transparent electrode material, enabling UV light-emitting diodes for a wide range of applications from water disinfection to polymer curing. It is demonstrated that Sr x NbO3 thin films can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…These performances have to be compared to those of SrNbO 3 (SNO) thin film, recently identified as a new performing TCO perovskite in ultraviolet range. [55,56] For SNO, the transmittance efficiency reaches 73% and makes it a good candidate for PV applications. Overall, the FOM and transmittance efficiency of our vanadate films integrated on glass is in the same order of magnitude as standard TCOs, demonstrating their excellent perfomances and the sustainability of this new integrating process for the next generation of TCOs such as vanadates or SNO.…”
Section: (6 Of 9)mentioning
confidence: 99%
“…These performances have to be compared to those of SrNbO 3 (SNO) thin film, recently identified as a new performing TCO perovskite in ultraviolet range. [55,56] For SNO, the transmittance efficiency reaches 73% and makes it a good candidate for PV applications. Overall, the FOM and transmittance efficiency of our vanadate films integrated on glass is in the same order of magnitude as standard TCOs, demonstrating their excellent perfomances and the sustainability of this new integrating process for the next generation of TCOs such as vanadates or SNO.…”
Section: (6 Of 9)mentioning
confidence: 99%
“…[ 7,8 ] Very recently, few studies on 4 d 1 SrNbO 3 also showed transparency in ultraviolet, but the investigation of infrared transmittance was missing. [ 13 15 ] Although diverse experimental findings have been reported in this rapidly expanding field, the availability of correlated metals with a wide transparency range is limited by the lack of design strategies and material candidates. It is therefore necessary to establish a unified and fundamental design principle to provide a basis for identifying correlated TCs with a wider transparency range.…”
Section: Introductionmentioning
confidence: 99%
“…These changes in the absorption profile coincide well with experimental and theoretical reports. 1 , 2 , 34 36 The first noticeable color change (from white to light blue, t < 0.5 h) is ascribed to the removal of surface defects that are periodically arranged within the lattice ( Figure 2 a). These defect sites are eliminated during the H 2 /Ar treatment, transforming the initially white powder (insulating) to a light blue (conductive).…”
Section: Resultsmentioning
confidence: 99%